International banking and cross-border effects of regulation: Lessons from Germany - Jana Ohls; Marcus Pramor; Lena Tonzer (Deutsche Bundesbank, 2016)
We analyze the inward and outward transmission of regulatory changes through German banks' (international) loan portfolio. Overall, our results provide evidence for international spillovers of prudential instruments, these spillovers are however quite heterogeneous between types of banks and can only be observed for some instruments. For instance, foreign banks located in Germany reduce their loan growth to the German economy in response to a tightening of sector-specific capital buffers, local reserve requirements and loan to value ratios in their home country. Furthermore, from the point of view of foreign countries, tightening reserve requirements was effective in reducing lending inflows from German banks. Finally, we find that business and financial cycles matter for lending decisions.
Keywords: F30; G01; G21; G28; 330; cross-border spillovers; prudential regulation; loan supply; German banks